Protection of Cultural Heritage in Turkish Private Law - Özsunay, Ergun (Cambridge University Press, 1997)
The Republic of Turkey has been trying for a long time to cope with preventing the smuggling and illicit traffic of cultural property. On the one hand, it endeavors to struggle against the looting of its archaeological sites; on the other hand, it tries to prevent theft of Turkish cultural properties by stricter enforcement of existing national laws and increasing sanctions. In spite of all these endeavours, it should be pointed out that Turkey is the largest sole source of antiquities for the American market.
Keywords: Kültür ve Tabiat Varlıkları Hukuku